Pencegahan Shivering Pada Pasien Dengan Anestesi Spinal Di Instalasi Bedah Sentral: Sequential Explanatory Model - Nuryanti, Aprilia; Ayuning Tias, Serli; Setyaningsih, Rahayu; Sudarmono, Andang (Yayasan Jompa Research and Development, 2025)
Shivering, or Post-Anesthesia Shivering (PAS), is one of the most common side effects of spinal anesthesia. Preventing shivering is crucial to avoiding complications such as patient discomfort, increased wound pain, delayed wound healing, elevated oxygen consumption, increased carbon dioxide production, and a higher metabolic rate. This study aims to identify both pharmacological and non-pharmacological interventions for shivering prevention. A mixed-method study with a sequential explanatory model was conducted in the Operating Theatre of a Type B hospital in Central Java over one month. The study involved 30 patients as respondents for the observational study and 9 anesthesia practitioners for the qualitative study. Data collection was carried out through patient observations and in-depth interviews with anesthesia practitioners. Shivering prevention interventions included pharmacological methods, with Pethidine (76.7%) as the most commonly used drug, followed by Tramadol, Dexamethasone, Ketamine, and Fentanyl. Additionally, non-pharmacological methods were implemented, including room temperature regulation (93.3%) and warmer blanket administration (93.3%). The qualitative study revealed that Pethidine was the preferred pharmacological choice for shivering prevention. Meanwhile, non-pharmacological strategies, such as warm infusions, oxygen administration, additional layers on the operating table, head caps, covering non-operated body parts, radiation, relaxation techniques, and deep breathing exercises, also played a significant role in reducing the incidence of shivering in spinal anesthesia patients. The findings of this study can serve as a guideline for shivering prevention management in IBS. Further research with a larger sample size, stricter control of shivering-related factors, and comparative studies on the effectiveness of various pharmacological and non-pharmacological interventions is recommended for a more comprehensive understanding.